IKLAN MEDIA TELEVISI DAN CITRA MEREK DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN PASTA GIGI PEPSODENT - Vitratin Vitratin; Bisri Merduani; Rianti Rianti (ECONOMOS, 2021)
This research is entitled Brand Image and Television Ads on Purchasing Decisions of Pepsodent Toothpaste. The purpose of this research is whether Brand Image and Television Advertising influence people's interest, how big is the influence of advertising and brand image on consumer purchasing decisions in Bandar Lampung. The method used in this study is to use multiple linear regression with views. The results obtained in this study are that the overall/simultaneous television and brand image ads affect the decision to purchase Pepsodent toothpaste and the influence of the remaining 42.8% is 57.2% influenced by other factors not examined and partially only influential television ads. on the purchase decision of Pepsodent Toothpaste, while Brand Image had no effect on Pepsodent Toothpaste Purchasing Decisions. Television advertising is able to reinforce the attitude towards Pepsodent toothpaste products, while respondents assume that brand image does not affect the purchasing decision of Pepsodent toothpaste because consumers buy it just to meet the needs, brand image has not been embedded in the minds of consumers, because respondents in this study are teenagers young) who only use products and consider brand image not important.